Islamic education governance towards independent learning: From creativity to innovation with a blended learning approach - Syahid, Abdul; Kafrawi, Kafrawi; Mulyadi, Mulyadi; Ilyas, Muhammad; Liriwati, Fahrina Yustiasari (International research journal of management, IT and social sciences, 2022)
Along with the development of knowledge and technology, today demands changes in all sectors, especially in the country’s governance of Islamic education. The author believes that today’s updated education governance is the implementation of technology-based learning, such as a blended learning-based approach. For this reason, we have completed a series of data searches from many publications or literature that discuss the issue of Islamic education and also the issue of learning through learning. Furthermore, our data were analyzed using a phenomenological approach to explore scientific evidence relevant to this study, after getting the data and reviewing it with a coding system of evaluation data, interpretation, and drawing conclusions that answer the study questions. Based on the existing data and additional discussions of this study, we can conclude that learning Islamic education governance from a creative learning community to innovation in educational services based on a blended approach learning has turned out to be a very innovative solution where technology has been able to transform learning, especially in an era that is being disrupted by various crises. It is hoped that this salary will become an essential input for examining studies and educational issues in the future.